Antibacterial effect and biocompatibility of silver nanoparticle-coated bone allograft substitutes: Antibacterial AgNPs for bone allograft infection - Hadi, Sanna; Omar, Othman (Cellular and Molecular Biology, 2024)
Osteoinduction, and/or osteoconduction, and antibacterial characteristics are prerequisites for achieving successful bone grafting. This study aimed to coat bone allografts with silver nanoparticles and assess their antibacterial activity and biocompatibility compared to uncoated bone allografts. In this study, the bone allografts were coated with varying concentrations of silver nanoparticles (5 mg/l, 10 mg/l, and 50 mg/l) through a simple adsorption technique. Subsequently, the coated samples underwent characterization using SEM, FTIR, EDS, and XRD. The Minimal Inhibitory Concentration (MIC) of the silver nanoparticles was determined against Staphylococcus aureus and Streptococcus mutans. Bacterial growth inhibition was evaluated by measuring turbidity and performing a disk diffusion test. Moreover, qualitative investigation of biofilm formation on the coated bone allograft was conducted using SEM. Following this, MG-63 cell lines, resembling osteoblasts, were cultured on the bone allografts coated with 5 mg/l of silver nanoparticles, as well as on uncoated bone allografts, to assess biocompatibility. The MIC results demonstrated that silver nanoparticles exhibited antimicrobial effects on both microorganisms, inhibiting the growth of isolates at concentrations of 0.78 mg/L for Staphylococcus aureus and 0.39 mg/L for Streptococcus mutans. The bone allografts coated with varying concentrations of silver nanoparticles exhibited significant antibacterial activity against the tested bacteria, completely eradicating bacterial growth and preventing biofilm formation. The osteoblast-like MG-63 cells thrived on the bone allografts coated with 5 mg/l of silver nanoparticles, displaying no significant differences compared to both the uncoated bone allografts and the control group. Within the limit of this study, it can be concluded that silver nanoparticles have a positive role in controlling graft infection. In addition, simple adsorption technique showed an effective method of coating without overwhelming the healing of the graft.